COVID-19 vaccine hesitancy in South Africa - Afari-Twumasi, Kwabena Kumi (University of the Witwatersrand, Johannesburg, 2024)
The purpose of this research was to examine why the level of COVID-19 vaccine hesitancy in South Africa is relatively high compared to the global average, despite more reassuring information being known about the safety and efficacy of the vaccines. This study zoned in on what factors most influence the decision to not get vaccinated against COVID-19 and what may influence the unvaccinated to change their mind. The overarching research problem was to develop effective strategies to move COVID-19 vaccine hesitants across the vaccine acceptance/rejection spectrum to the end where they are willing to get vaccinated. “Vaccine hesitancy refers to delay in acceptance or refusal of vaccination despite availability of vaccination services.” (MacDonald, 2015) The research looked at adults whose primary residency or occupation was in the Republic of South Africa. The entire survey was done via an anonymous online, largely Likert scale type, questionnaire. Most respondents were between the ages of 25 and 44 and had at least an undergraduate degree. There was an even balance between male and female respondents in the sample. Some of the key highlights revealed in the study were:  There is a fair level of distrust over government’s motives when it comes to the handling of the COVID-19 pandemic  About a third of respondents do not have conviction in the efficacy of the COVID-19 vaccines  Over half of respondents believe that mainstream media is unreliable or biased  Almost a quarter of all respondents have not been vaccinated  Common methods of encouraging the hesitant to vaccinate (e.g., Prohibiting travel to other countries) are unlikely to work in South Africa To improve COVID-19 vaccine uptake, the following recommendations were made:  Health authorities should keep educating people about why the vaccines are safe for human beings and how they can offer protection from serious illness or death  Health authorities should collaborate with mainstream media to build public trust. They should pay more attention to how the media portrays the pandemic to the public – the language used in reporting, the subject matter experts invited to speak, signs of bias, etc  Government should try to improve public trust in how they are handling the pandemic. One way to do this would be to make the decision making of the National Coronavirus Command Council (NCCC) more transparent to the public
A research report submitted in fulfillment of the requirements for the Master of Business Administration, In the Faculty of Commerce, Law and Management, School of Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: COVID-19; UCTD; South Africa; vaccine safety; mandatory vaccination; mainstream media perception; SDG-3: Good health and well-being